The Analysis of Early Childhood Teachers’ Pedagogical Content Knowledge - Ria Novianti; Febrialismanto Febrialismanto (Universitas Riau, 2020)
Pedagogical content knowledge (PCK) is the essential need of teaching and every teacher had to prioritized it for their teaching preparation. For early childhood education teacher, it is not only about knowledge of curriculum, instructional strategies and content, but also knowledge of students understanding. Teachers need to pay attention for all aspect in learning activities. With the awareness of PCK, teacher will have good performance while teaching and it will affect children understanding towards the subject. This research use descriptive quantitative methode to describe pedagogical content knowledge of 135 early childhood education teacher’s in Pekanbaru City that has been chosen by purposive sampling technique. Data collection and processing using google form. From four indicators of PCK, knowledge of student understanding score is the highest at 3,25, knowledge of instructional strategies score is 3,15, content knowledge score is 3.07 and knowledge of curriculum is the lowest with score 2,89. Emphaty and the ability to understand children comprehension in learning is pivotal for early childhood teacher. Young children don’t always express thought and emotion verbally, so teacher should also observed non verbal language and be thoughtful in order to help them understanding the subject. Early childhood teacher should gain more practiced and learn to enhance their knowledge of curriculum.